1996
DOI: 10.1212/wnl.46.2.559
|View full text |Cite
|
Sign up to set email alerts
|

Immune brachial plexus neuropathy

Abstract: We report brachial plexus biopsy findings from two Australian and two American patients with brachial plexus neuropathy. There were florid multifocal mononuclear inflammatory cell infiltrates. Present evidence suggests that these brachial neuropathies have an immune basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(101 citation statements)
references
References 4 publications
2
94
0
5
Order By: Relevance
“…To our knowledge, the findings from only five nerve biopsies performed during attacks of neuralgic amyotrophy have been reported in two studies 75,76 . In one of these reports, two patients had typical idiopathic neuralgic amyotrophy, and their brachial plexus biopsy samples revealed conspicuous mononuclear perivascular inflammation in the epineurium and endoneurium; no other histopathological features were detailed.…”
Section: Diabetic Lumbosacral Radiculoplexus Neuropathymentioning
confidence: 96%
“…To our knowledge, the findings from only five nerve biopsies performed during attacks of neuralgic amyotrophy have been reported in two studies 75,76 . In one of these reports, two patients had typical idiopathic neuralgic amyotrophy, and their brachial plexus biopsy samples revealed conspicuous mononuclear perivascular inflammation in the epineurium and endoneurium; no other histopathological features were detailed.…”
Section: Diabetic Lumbosacral Radiculoplexus Neuropathymentioning
confidence: 96%
“…17(p315) When evaluating a patient for possible PTS, the history should include a search for recent infection (including Epstein-Barr, Varicella Zoster, Dengue, and Hepatitis E viruses), immunization (tetanus toxoid, influenza), recent childbirth, prescribed medication (antiepileptics, antibiotics, immunosuppressants, antiretrovirals, and botulinum toxin), and all forms of surgery. 6,12,16,17 All of these are well documented to precede the onset of an attack of PTS and offer a valuable pointer toward the diagnosis if present, as was the case for surgery (37%) and infection (5%) in our series. Having decided upon a possible diagnosis of PTS, MRI imaging can be of use in ruling out alternative pathologies, including shoulder pathology or extrinsic nerve compression.…”
Section: Discussionmentioning
confidence: 58%
“…14,18 Effective treatment for PTS remains a distant ideal, but recent works have concentrated on abrogating the disease course with steroid and immunoglobulin therapy. 16,21 In a recent Cochrane update on PTS treatment, only 1 openlabel retrospective study demonstrated a possible benefit from steroid administration if given within 1 month of symptom development, with earlier pain resolution and faster recovery in some patients. 20 The high cost and associated problems with insurance reimbursement precluded the use of pharmacological agents such as immunomodulators in our series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Um estudo mostrou que os linfócitos de pacientes acometidos apresentavam aumento da sua atividade proliferativa (isto é, a transformação de linfócitos pequenos em células maiores que são capazes de sofrer mitose) em culturas com extratos de diferentes nervos do plexo braquial e seus ramos, mas não em culturas com extratos de nervos dos plexos sacrais. 18 Dois estudos mostraram infiltrados mononucleares inflamatórios em biópsias do plexo braquial, 19,20 ao passo que outro estudo mostrou aumento de anticorpos fixadores do complemento para a mielina do nervo periférico, na fase aguda da doença em três pacientes. 21 A forma hereditária da SPT é autossômica dominante e é causada por mutações no gene septin 9 no cromossomo 17q23.…”
Section: Etiologiaunclassified